Malignant Renal Tumors in Childhood: Report of 54 Cases Treated at a Single Institution - Tang-Her Jaing; Iou-Jih Hung; Chao-Ping Yang; Jin-Yao Lai; Chen-Kan Tseng; Tsung-Yen Chang; Chuen Hsueh; Pei-Kwei Tsay (Elsevier, 2014)
Wilms tumor is the most common primary renal malignancy occurring in childhood. Significant improvement has been made in the treatment of children with Wilms tumor. However, the treatment of patients with non-Wilms renal tumors remains challenging. Methods: Between 1991 and 2010, 70 children with renal tumors were diagnosed at a single institution. Fifty-four patients were histologically confirmed and divided into three groups, including 42 Wilms tumors, seven clear cell sarcomas of kidney, and five malignant rhabdoid tumors. Most patients underwent unilateral nephrectomy and lymph node sampling followed by adjuvant chemotherapy. Twenty-one of these patients subsequently received radiotherapy. Results: During follow-up, 12 patients died of progressive disease and one died of operative mortality. One patient with unilateral pleural metastases subsequently underwent hematopoietic stem cell transplantation. The median survival time of all patients was 88 months. Children under 2 years of age at diagnosis with Wilms tumor or clear cell sarcoma of kidney had an excellent survival rate of 100% compared to the 0% survival rate of MRT. Conclusion: Younger age at diagnosis bore a better prognosis than did older age, whereas a diagnosis of malignant rhabdoid tumor portended a worse prognosis. Younger patients and appropriate treatment may have contributed to the improved prognosis of clear cell sarcoma of kidney.